POLARITY EFFECT ON CORONA DISCHARGE VOLTAGES IN SF6- N2 GAS MIXTURES - M. Assia Guerroui; Ahcene Lemzadmi (European Scientific Journal, ESJ, 2013)
This work is to investigate the behaviour of SF6-N2 mixtures that can be considered as a potential substitute of pure SF6. The inception voltages have been determined from the measurements of the current-voltage characteristics for both polarities under high pressures and with highly inhomogeneous fields. The results show that the onset voltages increase with the increase of the gas pressure and the values of positive polarity are higher to those obtained with negative polarity.